PEMBAGIAN HARTA WARIS PADA SUKU BUGIS DI DESA PENGALIHAN KECAMATAN KERITANG KABUPATEN INDRAGIRI HILIR - Said Muhammad Iqbal; Hayatul Ismi; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Adat is a reflection of the personality of a nation, and is one of the incarnations ofthe soul of the nation concerned from century to century, therefore each nation in thisworld has its own customs that are not the same. The division of inheritance in the Bugistribe follows the patrilineal system or the father's lineage, which means that boys get agreater share than girls. The division of inheritance includes houses, land and otherproperty, girls in the Bugis tribe only get the inheritance from the heir while the boys get alarger share of land and other assets. In the customary distribution of inheritance to thewidow or widower Bugis tribe does not get a share, they are only allowed to manage theinheritance for the survival of the heirs. The emergence of a dispute in the distribution ofinheritance to the Bugis tribe occurs because the girl feels she is entitled to other assets,the desire to get equality distribution of inheritance or inheritance is shared equally orfairly.The problem that the author makes the basis in this study is how the distribution ofinheritance to the Bugis tribe community in the Village Transfer of Kritang District,Indragiri Hilir Regency, how the process of resolving the dispute over the distribution ofinheritance to the Bugis tribe community in the Transfer of the Kritang District, IndragiriHilir Regency. This type of research can be classified into empirical or sociologicalresearch types, because in this study the author directly conducts research at the locationor place of study in order to provide a complete and clear picture of the problem understudy. This research was conducted in the Village Transfer of Kritang sub-district,Indragiri Hilir Regency, the source of the data used are primary data and secondary data,data collection techniques in this study by observation, interviews and literature review.The results of this study are first. The distribution of the inheritance of the Bugistribe in Pengransfer village, Keritang Subdistrict, Indragiri Hilir Regency is done in threeways including the following, first is done by Grant (Pabbere), second by Wasiat(Pappaseng), and the last by After After Death / Deliberation Heir (Deliberation) where totalk). In the distribution of inheritance from the Bugis tribe in Pengransfer village,Keritang Subdistrict, Indragiri Hilir Regency, the ratio of inheritance received by girlsand boys is not balanced, which is two to one. Secondly, the improper distribution ofinheritance between boys and girls often results in disputes where girls feel inadequatewith their inheritance, the settlement of inheritance disputes in the Bugis customaryvillage in Pengalih Subdistrict Keritang, Indragiri Hilir Regency is done in two ways, firstby means of Family Consultation (Tudang Sipulung) By customary consultation(mapahkiade)Keywords: inheritance, adat, bugis tribe